Isolasi dan Karakterisasi Bakteri Endofit dari Batang Talas (Colocasia esculenta L.) - Pakh, Jusanty Antoneta; Manalu, Adelya Irawan; Pardosi, Lukas (Program Studi Biologi, Universitas Timor, 2023)
TARO (COLOCASIA ESCULENTA L.) IS A TYPE OF TUBER THAT IS USED AS A TRADITIONAL MEDICINE TO TREAT VARIOUS DISEASES. THIS PLANT CONTAINS SECONDARY METABOLITES, INCLUDING ALKALOIDS, TANNINS AND FLAVONOIDS. THE PURPOSE OF THIS STUDY WAS TO DETERMINE THE ANTIBACTERIAL POTENTIAL OF ENDOPHYTIC BACTERIAL ISOLATES FROM TARO (COLOCASIA ESCULENTA L.) ON THE GROWTH OF PATHOGENIC ESCHERICHIA COLI BACTERIA. THE STAGES IN THIS STUDY WERE THE ISOLATION OF ENDOPHYTIC MICROBES FROM TARO PLANTS, ANTIMICROBIAL TESTING USING THE AGAR DIFFUSION METHOD, BIOCHEMICAL CHARACTERIZATION INCLUDING IDENTIFICATION OF COLONY MORPHOLOGY AND CELL MORPHOLOGY. THE MEDIA USED FOR THE ISOLATION OF ENDOPHYTIC BACTERIA IS NUTRIENT AGAR (NA). THE ISOLATES OBTAINED WERE THEN SUBJECTED TO ANTIMICROBIAL TESTS USING THE AGAR DIFFUSION METHOD, AND THE COST OF INHIBITION. Keyword: TARO, ENDOPHYTIC BACTERIA, ANTIMICROBIAL